Identifikasi dan penentuan kadar chloramphenicol pada udang vannamei (litopenaeus vanname) di PT K&Q Indolab - Islamiyani, Annisa; Saing, Bungaran; Masrida, Reni (Trend and Future of Agribusiness, 2024)
Background: White shrimp (L. vannamei) is an introduction species that is widely cultivated in Indonesia and is the highest export commodity of other types of shrimp. The presence of the residual antibiotic chloramphenicol in some shrimp products exported from Indonesia is prohibited. The shrimp's intensive maintenance system leads to a high use of antibiotics in shrimp cultivation. Chlorampenicol is added to disinfectant and shrimp feed. When these shrimp are consumed, residues of antibiotics can cause a variety of dangers. As a result, research that can guarantee sustainable food security is needed. This study was conducted to determine the level of chloramphenicol residues in the Vanamei shrimp. The research was conducted at K&Q Indolab. Methods: The method used in this study is ELISA (enzyme-linked immunoassay). ELISA is a detection technique with a serological method that is based on specific reactions between antigens and antibodies and has high sensitivity and specificity using enzymes as indicators. Findings: Test results of chloramphenicol residues on frozen white shrimp products on two different samples of Vandamei shrimp. Conclusion: The results indicate that the level of chloramphenicol in Vannamei shrimp is still below the International Standard in accordance with Commission Decision 2003/181/EC, which is 0.3 ppb.